Assessing Financial Distress: The Role of Financial Ratios & Managerial Ownership - Thio Anastasia Petronila; Difanda Putra Wicaksana; Juliana, Christina (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The aim of this research is to examine the effect of the current ratio, debt-to-asset ratio, and company size on financial distress, with managerial ownership as a moderating variable. The research population consists of infrastructure companies listed on the Indonesia Stock Exchange from 2019 to 2022, while the sample includes 28 companies, totaling 103 observation data points, selected using the purposive sampling method and casewise diagnostics. Data analysis is conducted using descriptive statistics and the moderated regression analysis method. Financial distress is measured using the modified Altman Z-Score. The analysis findings indicate that the current ratio has a negative effect on financial distress, while the debt-to-asset ratio has a positive effect. However, company size has no significant effect on financial distress. Furthermore, managerial ownership does not moderate the effects of the current ratio, debt-to-asset ratio, or company size on financial distress.